1990
DOI: 10.1007/bf00177842
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for malignant glioma using human recombinant interleukin-2 and activated autologous lymphocytes

Abstract: Over the past few years, we and a number of other groups have conducted laboratory experiments and clinical trials of human recombinant interleukin-2 (rIL-2) alone or in combination with autologous 'activated' lymphocytes expressing in vitro tumoricidal activity in order to define toxicity and indicate its potential efficacy in patients with high-grade glioma. Because high rIL-2 concentrations can be attained with considerably less toxicity than with a systemic approach, all of the clinical trials, to date, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 66 publications
(67 reference statements)
1
28
1
1
Order By: Relevance
“…The need for new therapies has led investigators to study the specificity and efficacy of immune-mediated tumor destruction. While immunotherapeutic strategies against glioblastomas have been promising both in vitro (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and in animal models (14 -20), similar successes have not been realized in human clinical trials (17,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 98%
“…The need for new therapies has led investigators to study the specificity and efficacy of immune-mediated tumor destruction. While immunotherapeutic strategies against glioblastomas have been promising both in vitro (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and in animal models (14 -20), similar successes have not been realized in human clinical trials (17,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 98%
“…Their clinical effectiveness, however, has been limited because of the short half-life (about 20 min), the small fraction of the systemically administered dose reaching the tumor at an effective concentration, and their systemic toxicities. Other treatment modalities, including immunotherapy, immunoradiotherapy, and gene therapy, are under development but burdened with the problem of drug delivery across the blood-brain barrier Culver et al, 1992;Fontana et al, 1992;Jachimczak et al, 1993;Köppen et al, 1991;Kramm et al, 1995;Laske et al, 1997;Liebermann et al, 1995;Martuza, 1997;Merchant et al, 1990Merchant et al, , 1997Mesnil et al, 1996;Rainov, 2000;Ram et al, 1997;Reist et al, 1995;Riva et al, 1997;Wersall et al, 1997). In spite of the numerous therapies administered, the median survival of patients with high-grade gliomas is approximately one year (Brada and Yung, 2000;Hildebrand et al, 1997;Levin et al, 1997).…”
mentioning
confidence: 99%
“…Jeffes et al [8] reported that 3 of 11 patients had a decrease in tumor size of 7 of 11 patients with recurrent high-grade glioma clinically improved after treatment with IL-2-stimulated killer cells. Merchant et al [9] treated 29 patients with brain tumors with intercavitary IL-2 LAK/treatment. Three of the 29 patients required a second surgical resection for uncontrollable cerebral ede ma and clinical deterioration.…”
Section: Adoptive Immunotherapymentioning
confidence: 99%